THE MEANING OF SELECTED MIRACLES OF THE QUR'AN THROUGH THE EYES OF COMPUTER ENGINEERING. - Karlık, Bekir (Al-Shajarah: Journal of the International Institute of Islamic Thought & Civilization, 2018)
Currently, all scientific and technological developments and discoveries continue to confirm the miraculous verses of the Holy Qur'an. Indeed, the Qur'an, since time immemorial will continue until the Day of Judgment. Allah (S.W.T) has infinite knowledge that encompasses everything in the heavens and earth and what is in between them; in the worldly life and the Hereafter.3 As in all fields of technology, the latest developments in the field of computer engineering, the Holy Qur'an has shed light on different interpretations of some verses. This study presents explanations of some interpretation of the miracles contained in the Holy Qur'an through the eyes of computer engineering.